Green Practices Of Water And Energy On Sustainable Tourism Development: A Case Study Of 5-star Hotels In Hurghada And Mecca - Mahmoud Abouamer, Adel Mohamed (2024)
The study examines the green practices (water & energy) in hotels and their effect on the sustainable tourism development in Mecca and Hurghada. The study aimed to identify the green energy and water practices that 5-star hotels in Hurghada, Egypt, and Mecca; determine the challenges they face hotels in implementing green practices affect the overall development of sustainable tourism; and examine how the successful implementation of green practices in hotels benefits the development of sustainable tourism at the 5-star hotel's levels. A qualitative research method was applied: namely, Focused Group Discussions (FGDs) and Semi-Structured Interviews (SSIs) as data collection techniques. The total sample was (18) respondents who were managers, owners of hotels, heads of departments directly involved in daily operations, and a few researchers from the same field. The responses obtained from the FGDs and SSIs were then segregated into the relevant themes and sub-themes. Findings showed that 5-star hotels in Hurghada and Mecca conduct different green practices-related training for their staff, display signboards, decrease the use of electric equipment, upgrade to solar-powered energy systems, and create operating schedules for their lighting and air conditioning systems.